2020
DOI: 10.1186/s12889-020-08620-w
|View full text |Cite
|
Sign up to set email alerts
|

Associations between meeting sleep, physical activity or screen time behaviour guidelines and academic performance in Australian school children

Abstract: Background: Current guidelines suggest too little sleep, too little physical activity, and too much sedentary time are associated with poor health outcomes. These behaviours may also influence academic performance in school children. The primary purpose of this study was to examine the relationships between sleep, physical activity, or sedentary behaviours and academic performance in a school with a well-developed and integrated technology use and well-being program. Methods: This was a cross-sectional survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 44 publications
1
43
2
3
Order By: Relevance
“…Only 5.4% of adolescents (5.9% boys and 4.8% girls) met the three 24-Hour Movement Guidelines, while 10.2% of adolescents (10.3% of boys and 10.1% of girls) did not meet any of these three recommendations. The adherence to 24-Hour Movement Guidelines found in our study is higher than those found in the studies conducted with European [ 17 , 19 , 27 ] and Asian adolescents [ 14 , 21 , 26 ] and lower than several studies conducted in the United States (5.0%–9.4%) [ 16 , 22 , 23 ]. However, our results are similar to the results found in Canadian adolescents [ 15 , 18 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Only 5.4% of adolescents (5.9% boys and 4.8% girls) met the three 24-Hour Movement Guidelines, while 10.2% of adolescents (10.3% of boys and 10.1% of girls) did not meet any of these three recommendations. The adherence to 24-Hour Movement Guidelines found in our study is higher than those found in the studies conducted with European [ 17 , 19 , 27 ] and Asian adolescents [ 14 , 21 , 26 ] and lower than several studies conducted in the United States (5.0%–9.4%) [ 16 , 22 , 23 ]. However, our results are similar to the results found in Canadian adolescents [ 15 , 18 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 92%
“…However, most existing studies have reported that less than 10% of adolescents met the 24-Hour Movement Guidelines [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. These aforementioned studies have found inconsistent results in the proportion of adolescents who meet the 24-Hour Movement Guidelines, which have ranged from 0.3% to 2.0% in Asian [ 14 , 21 , 26 ] 3.1% in South Americans [ 25 ], 2.2% to 9.4% in North Americans (ranging from 2.2% to 5.2% in Canadian and from 5.0% to 9.4% in American) [ 4 , 15 , 16 , 18 , 22 , 23 , 24 , 28 , 29 , 30 , 31 , 32 , 33 ], and from 1.7% to 2.2% in European [ 17 , 19 , 27 ]. Most adolescents met sleep duration recommendations [ 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 25 ,…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research shows that children exceed those screen time recommendations [29][30][31][32][33][34], and studies investigating health outcomes related to screen time indicate that high screen time is associated with increased weight gain and obesity [30,[35][36][37][38][39]. Consequently, reducing children's sedentary time (including screen time) may be important for the prevention of chronic diseases even in adulthood [40].…”
Section: Introductionmentioning
confidence: 99%